(untitled) (World Bulletin of Social Sciences, 2024)
In this article, the analytical result of the use of drip irrigation, which is currently used in cotton cultivation, is presented. The positive aspects of the technology of using drip irrigation in the cotton field for effective and rational use of water resources are highlighted. The demand for water resources is increasing year by year due to factors such as population growth, increased food demand, expansion of industrial production, and climate change in the countries of the world. As a result, the world itself is experiencing water shortages. Taking into account the water demand of cotton grown in Kashkadarya region, the standard of use of available data from weather station data using FAO method CropWat 8.0. Based on the mechanical composition of the soil, the software of seepage and cleaning, the mineral resources of cotton are obtained. The results of scientific research conducted by scientists in cotton fields were analyzed in Kham. In addition, scientifically based irrigation methods of water-saving irrigation technology of cotton were developed according to the generally accepted hydromodule region for the conditions of Kashkadarya.